RELASI SOSIAL ANTARA PETANI NANAS DENGAN PEDAGANG NANAS DI DESA GALANG KABUPATEN MEMPAWAH - Kristina Kiki Kosella; Yohanes Bahari; Nining Ismiyani (Universitas Tanjungpura, 2022)
This study aims to determine the social relantions between peneaple farmers and peneaple treders in Galang Village,Sungai Pinyuh District. The research method used in this study is qualitative research methods. The sample of data in this study are peneapple farmers and peneapple treders in Galang Village. Data collection techniques in this study are observation, interview, and documentation, while the tools used in data collection are observation guides, interview guides and notebooks. The analysis in this study is presented in a qualitative descriptive. The sample are 6 informants, consisf 3 pineapple farmers and 3 pineapple trades in Galang Village. The results of this study are between pineapple farmers and pineapple trades had social relantionship, that are cooperation, accomodation, assimilation, and acculturation. Besides that there are also had some factors to made good relations between farmers and traders, namely attitude of trust and sportsmanship. But in this social relantionship had many obstacles there are stereotype barriers and prejudice barriers. Keywords: Social Relations, farmers, Traders